DNA gap repair in Escherichia coli for multiplex site‐directed mutagenesis. Issue 5 (13th March 2020) - Lyozin, George T.; Brunelli, Luca
Abstract: Site‐directed mutagenesis allows the generation of novel DNA sequences that can be used for a variety of important applications such as the functional analysis of genetic variants. To overcome the limitations of existing site‐directed mutagenesis approaches, we explored in vivo DNA gap repair. We found that site‐specific mutations in plasmid DNA can be generated in Escherichia coli using mutant single‐stranded oligonucleotides to target PCR‐derived linear double‐stranded plasmid DNA. We called this method DeGeRing, and we characterized its advantages, including non‐biased multiplex mutagenesis, over existing site‐directed mutagenesis methods such as recombineering (recombination‐mediated genetic engineering), single DNA break repair (SDBR, introduced by W. Mandecki), and QuikChange (Agilent Technologies, La Jolla, CA). We determined the efficiency of DeGeRing to induce site‐directed mutations with and without a phenotype in three K‐12 E coli strains using multiple single‐stranded oligonucleotides containing homological and heterological parts of various sizes. Virtual lack of background made the isolation of mutants with frequencies up to 10 ‐6 unnecessary. Our data show that endogenous DNA gap repair in E coli supports efficient multiplex site‐directed mutagenesis. DeGeRing might facilitate the generation of mutant DNA sequences for protein engineering and the functional analysis of genetic variants in reverse genetics.